BLACK SOYA BEAN AND BLACK CHIA SEEDS AS A SOURCE OF NUTRIENTS AND BIOACTIVE COMPOUNDS WITH HEALTH BENEFITS - Nikolić, Valentina (Food and Feed Research, 2020)
Recent trends in healthy lifestyle and diet made functional foods rich in quality nutrients and bioactive compounds with potential health benefits highly sought after. Some cultivated plants, such as soya and chia can provide a viable source of nutraceuticals with high fibre, protein, and protective antioxidant potential. The whole-grain flours of black soya beans and black chia seeds were used in this study. Potential nutritive and health-benefitting properties of these flours were compared by assessing their chemical composition and antioxidant profile. The content of dietary fibres such as NDF, ADF, ADL and hemicellulose determined in black chia seed sample was higher than in black soya soya beans which had higher fibre content. The total protein content recorded in black soya beans was almost as twice as high (42.26+0.14%) as chia protein content (25.04+0.20%). Black soya beans had the highest content of water soluble proteins (29.00+0.13% d.m.) with NSI (nitrogen solubility index) acounting for as much as 70.96+0.31% of total proteins, while black chia seeds had the highest content of globulins (14.64+0.07% d.m.) and NSI 58.48+0.27% of total proteins. Both black soya bean and black chia contained a high amount of total phenolic compounds (830.66+5.46 and 1201.94+16.29 mg GAE/kg, respectively) and exhibited a considerable total antioxidant capacity, which makes them good contestants for functional food ingredients with potential health benefits.